Comparative analysis of translation on harf jar al ba'in surah al kahf by Abdullah Yusuf Ali and Muhammad Marmaduke Pickthall - Muhammad Wahyu Al Aziz (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2019)
etik,1./ws.c.1